Characterization of Growth Behavior and the Resulting Forces Applied by Pollen Tubes in a 3D Matrix - Reimann, Ronny; Kah, Delf-Thorge Eric (Pollen and Pollen Tube Biology, 2020)
The question of how pollen tubes orient themselves on their way to the egg cell is a major focus of plant reproduction research. The role of physical guidance through the tissues of the pistil in relation to the mechanical perception and growth adaptation of the pollen tubes has not been sufficiently investigated. In order to advance research on the mechanical perception of pollen tubes and their force application during invasive growth, we present simple methods for the observation and mechanical characterization of pollen tubes in vitro, which can be established with little effort in any biological laboratory with standard equipment. Pollen grains are germinated in a hydrogel containing agarose and their growth is recorded in 3D using brightfield microscopy. Using suitable analysis software, parameters such as growth rate and pollen tube diameter can then be determined to estimate the exerted penetration force.
CRIS-Team Scopus Importer:2020-06-23
Keywords: 3D matrix; Agarose; ClickPoints; Force measurement; Hydrogel; Indentation; Mechanical guidance; Microindenter; Polar growth; Pollen tube; Single cell